The Adiponection/Leptin Ratio and Insulin Resistance among Mongolians with Metabolic Syndrome - Dagdan, Batnaran; Chuluun-Erdene, Ariunbold; Malchinkhuu, Munkhzol; Janlav, Munkhtsetseg (Central Asian Journal of Medical Sciences, 2018)
Objectives: In this study, we aimed to determine the relationship between adiponectin/leptin (A/L) ratio and insulin resistance among Mongolian subjects with metabolic syndrome (MetS). Methods: The study was comprised of 364 adults. Fasting blood glucose, total cholesterol, triglyceride, and high density lipoprotein cholesterol were measured. Serum adiponectin and leptin were measured using enzyme-linked-immunoassay. Low density lipoprotein cholesterol and homeostatic model assessment-insulin resistance (HOMA-IR) were calculated. Results: Serum adiponectin was inversely correlated with diastolic blood pressure, body mass index, waist circumference, serum triglyceride, and fasting insulin level (r=-0.118, r=-0.190, r=-0.244, r=-0.231, and r=-0.165, respectively) (p<0.001). Serum leptin was significantly correlated with all risk factors of metabolic syndrome, except for lipid parameters (p<0.001). In the multiple regression analysis, HOMA-IR was significantly associated with adiponectin and A/L ratio among males with MetS, after adjustment for other factors. Conclusion: The A/L ratio was a significant predictor for insulin resistance among male adults with MetS.